Diagnóstico de la vivienda para estudiantes universitarios en la ciudad de Riobamba dentro del marco conceptual de una ciudad Universitaria - Joselyn Fernanda, Miranda Olivo (2019)
The objective of this research is to diagnose the characteristics and conditions of student housing in their, specifics spaces complementary of the Riobamba city, within the framework of the declaration as a university city. For this, a survey is performed to immigrant students of Universidad Nacional de Chimborazo and Escuela Superior Politécnica de Chimborazo, architectural floor plans are technically analyzed, and the dwelling is georeferenced indicating their quality. Among the main results of physical space, functional analysis, physical and functional technician it is noted that there is no compliance whit minimum dimension, ventilation or lighting of spaces rented to students due to transformation of building, which impacts on the housing quality, as the lacking of urban equipment to get better students necessities. As a conclusion, there is a lack of control and planning of architectural and urban development to cover the declaration as a university city, as there is no adequate provision of housing in the private market that meets the minimum construction regulations and guarantees university students a good quality of accommodation.